Is taper corrosion in modular revision hip stem junctions associated with patient or implant specific factors?: a retrieval analysis - Bormann, Therese; Kretzer, Jan Philippe; Jäger, Sebastian; Lohmann, Christoph H. (Journal of the mechanical behavior of biomedical materials, 2024)
Implant modularity within revision total hip arthroplasty (THA) offers multiple implant configurations and allows surgeons a high intraoperative flexibility to restore functionality to the patients joint, even in complex revision cases. However, a rare but devastating complication for patients, clinicians and manufacturers presenting a breakage of the taper junction between the distal stem and the proximal implant part. Aside from implant and patient specific risk factors, corrosion and fretting at the stem junctions have been associated with taper failure. Whether corrosive processes are a precursor of failure or rather an accompaniment of material fatigue is thereby still unclear. Therefore, this study aims to investigate the incidence of taper corrosion in a collection of 17 retrievals from a single type (MRP-Titan, Peter Brehm GmbH) and on the correlation of taper corrosion to implant and patient specific factors. None of the implants was revised for problems related to the taper junction, corrosion or the implant itself. The modular stem junction of all retrievals was visually rated with respect to corrosion, fretting and surface contamination. Additionally, the stability of taper junctions of retrievals where the proximal part with the neck was still assembled to the stem was determined by measuring the loosening moment of the securing screw and the push-out-force for taper dissociation. There was no difference between the mean push-out-force of the retrievals (14 kN +/- 1.2 kN) and new reference samples (12.6 kN +/- 0.5 kN). Approximately one third of the investigated retrievals showed considerable taper corrosion. The extent of corrosion increased with time in vivo and contamination of the neck piece, while it decreased with the loosening moment of the locking screw. The parameters femoral head offset, neck piece length, lateralized neck pieces, obesity of patients and septic/aseptic revision were not correlated to taper corrosion. Taper corrosion seems to occur regularly in modular taper junctions and is not necessarily connected to taper failure. A correct assembly of the junction and avoiding taper surface contamination during revision surgery is mandatory.
Gesehen am 20.08.2024